2016
DOI: 10.18632/oncotarget.11016
|View full text |Cite
|
Sign up to set email alerts
|

miR-450b-5p induced by oncogenic KRAS is required for colorectal cancer progression

Abstract: The development and progression of CRC are regarded as a complicated network and progressive event including genetic and/or epigenetic alterations. Recent researches revealed that MicroRNAs are biomarkers and regulators of CRC progression. Analyses of published microarray datasets revealed that miR-450b-5p was highly up-regulated in CRC tissues. In addition, high expression of miR-450b-5p was significantly associated with KRAS mutation. However, the role of miR-450b-5p in the progression of CRC remains unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 52 publications
2
25
0
1
Order By: Relevance
“…Although alterations such as gene amplification, deletion, and translocation are common events in genomic regions hosting miRNAs and can influence their expression in cancer (66), direct regulation by oncogenes and tumor suppressors can also significantly influence miRNA expression levels (27)(28)(29)(30)(31). Previous studies have suggested upregulation and functional roles for miR21, miR450b-5p, and miR30c in response to oncogenic KRAS in cancer (14)(15)(16)(17). Here we used primary MEFs with conditional expression of oncogenic KRAS (36) to identify key dysregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although alterations such as gene amplification, deletion, and translocation are common events in genomic regions hosting miRNAs and can influence their expression in cancer (66), direct regulation by oncogenes and tumor suppressors can also significantly influence miRNA expression levels (27)(28)(29)(30)(31). Previous studies have suggested upregulation and functional roles for miR21, miR450b-5p, and miR30c in response to oncogenic KRAS in cancer (14)(15)(16)(17). Here we used primary MEFs with conditional expression of oncogenic KRAS (36) to identify key dysregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism for regulation of gene expression is via microRNAs (miRNAs) (13). However, our understanding of the role of miRNAs functionally regulating the consequences of KRAS activation is still limited (14)(15)(16)(17). The study of miRNA function is an alternative strategy to yield molecular insights necessary for the development of novel therapies against KRAS-driven tumors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Siah1 is a target of MiRNAs [9][10][11] and other proteins [12] that are likely to affect the occurrence and progress of tumor [13]. Recent studies [14][15][16][17][18] have found that Siah1 plays an important role in promoting apoptosis under hypoxic conditions or by the P53-induced pathway, and during the process of tumor development, Siah1 behaves as a tumor suppressor.…”
mentioning
confidence: 99%